2009
DOI: 10.1051/0004-6361/200811481
|View full text |Cite
|
Sign up to set email alerts
|

The influence of longitudinal density variation in coronal loops on the eigenfunctions of kink-oscillation overtones

Abstract: Context. As coronal loops are spatially at least partially resolved in the longitudinal direction, attempts have been made to use the longitudinal profiles of the oscillation amplitudes as a seismological tool. Aims. We aim to derive simple formulae to assess which oscillation modes and which quantities of the oscillation (displacement or compression) are most prone to modifications induced by stratification of the equilibrium density along the loop. We furthermore clarify and quantify that the potential of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…It shows that as a result of density stratification, the anti-nodes of the first-overtone eigenfunction shift away from the loop apex (z = 0). This result was also obtained by Andries et al (2009) for kink modes. Figure 7 clears also that in the presence of magnetic field expansion, the anti-nodes shift towards the loop apex which is in agreement with the result obtained by Verth and Erdélyi (2008) for the kink body modes.…”
Section: Numerical Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…It shows that as a result of density stratification, the anti-nodes of the first-overtone eigenfunction shift away from the loop apex (z = 0). This result was also obtained by Andries et al (2009) for kink modes. Figure 7 clears also that in the presence of magnetic field expansion, the anti-nodes shift towards the loop apex which is in agreement with the result obtained by Verth and Erdélyi (2008) for the kink body modes.…”
Section: Numerical Resultssupporting
confidence: 81%
“…For instance, it was pointed out by Verth (2007) that if the magnetic field becomes weaker towards the loop apex, a useful magneto-seismological signature is the anti-node of the 1st harmonic since it shifts towards the loop apex. Also Andries et al (2009) used the anti-node shift in the presence of longitudinal density stratification as signature of the eigenmode modifications. They showed that the anti-node shift of the eigenfunctions of the higher kink- Fig.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Hollweg and Yang 1988;Ruderman and Roberts 2002;Van Doorsselaere et al 2004), while axial stratification affects the periods of oscillation (see e.g. Andries et al 2005aAndries et al , 2005bAndries et al , 2009aAndries et al , 2009bArregui et al 2005;Goossens et al 2006;Dymova and Ruderman 2005, 2006a, 2006bMcEwan et al 2006McEwan et al , 2008Ruderman et al 2008).…”
Section: Resonant Mhd Waves With Mixed Propertiesmentioning
confidence: 99%
“…E.g., L = 100 Mm and H = 50 Mm causes a shift of 5.6 Mm, well within the resolution of TRACE (714 km). This was taken up further by Andries et al (2009) anticipating possible detection of higher overtones in the future. Carrying out a linear expansion of the eigenfunctions in the stratification parameter α (as had done earlier for the frequency), an approximation is found for the lth Fourier contribution in the kth mode with k and l arbitrary.…”
Section: Spatial Seismologymentioning
confidence: 99%
“…Another interesting development concerns the use of the longitudinal eigenfunctions as seismological tools Safari et al 2007;Andries et al 2009). Although its application is subject to considerably more observational uncertainty, it is most certainly an avenue that must be considered.…”
Section: Introductionmentioning
confidence: 99%